Level of Knowledge of Pregnant Women About Anemia in the Working Area of the Pangkalan Baru Community Health Center, Bangka Belitung Islands - Oktavia, Liana Devi; Lubis, Astri Yulia Sari (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this researchto determine the level of knowledge and characteristics of pregnant women regarding anemia in the Pangkalan Baru Community Health Center Working Area. This type of research is descriptive with a cross sectional approach. The total population was 34 pregnant women in the working area of the Pangkalan Baru community health center, taken using total sampling technique. The data collection method uses guided interviews. The research results showed that 61.8% of respondents had sufficient knowledge, 85.3% of respondents' age range was 20-35 years, 50% of respondents had a high school education, 94% of respondents' parity was <3, and 97.1% of respondents were housewives. The conclusion is that the level of knowledge of pregnant women about anemia in the work area of the Pangkalan Baru Community Health Center is in the sufficient category, namely 21 respondents (61.8%).